2016
DOI: 10.1111/cea.12781
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic randomized controlled trial of an allergy intervention for children aged 6–16 with asthma and rhinitis in general practice

Abstract: Summary Background It is widely believed that for allergic rhinitis and asthma, avoidance of specific triggers can improve symptom control. Whilst many children with asthma or rhinitis are sensitized to airborne allergens, primary care diagnostic and management decisions are often made without a detailed history of the allergic triggers or allergy testing. Thus, treatment decisions are empirical and allergen avoidance advice is either not given or, if given, not tailored to the child's sensitivities. Objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…31 The evidence however suggests that treatment of allergic rhinitis does not improve asthma symptoms in either children or adults where both conditions co-exist. 32 Home visits are important because they allow the asthma team to get an impression of the home environment. The visit can identify ongoing allergen exposure to dust, moulds, pets, exposure to second hand tobacco smoke or vaping and other pollutants.…”
Section: Comorbiditiesmentioning
confidence: 99%
“…31 The evidence however suggests that treatment of allergic rhinitis does not improve asthma symptoms in either children or adults where both conditions co-exist. 32 Home visits are important because they allow the asthma team to get an impression of the home environment. The visit can identify ongoing allergen exposure to dust, moulds, pets, exposure to second hand tobacco smoke or vaping and other pollutants.…”
Section: Comorbiditiesmentioning
confidence: 99%
“…A significant proportion of clinical allergy services is devoted to making an accurate diagnosis, and the value of this is sometimes called into question. In a randomized controlled trial of allergy testing and appropriate allergen avoidance advice, for children aged 6‐16 years with allergic rhinoconjunctivitis or asthma, Smith et al identified clear, measurable improvements in rhinitis symptoms and quality of life 1 year after the intervention, thus supporting the value of allergy testing, when combined with appropriate interpretation and avoidance advice.…”
Section: Clinical Allergymentioning
confidence: 99%
“…Twenty general practices in two different English cities performed a RCT of 335 children aged 6–16 years suffering from allergic asthma and/or rhinitis to compare the effectiveness of allergen-specific interventions vs usual care (51). Specific allergen avoidance strategies (for tree and grass pollens, pets, HDM, or molds) were provided according to allergy history and SPT.…”
Section: House Dust Mitesmentioning
confidence: 99%
“…Specific allergen avoidance strategies (for tree and grass pollens, pets, HDM, or molds) were provided according to allergy history and SPT. After 1 year, patients receiving specific allergy intervention showed fewer nasal symptoms and a higher QoL index, while no significant changes were observed in bronchial symptoms, health-care utilization, or number of days with impaired daily activities (51). …”
Section: House Dust Mitesmentioning
confidence: 99%